2020
DOI: 10.1007/s00134-019-05867-9
|View full text |Cite
|
Sign up to set email alerts
|

Inter-country variability over time in the mortality of mechanically ventilated patients

Abstract: Purpose: Variations in clinical characteristics and management and in the mortality of mechanically ventilated patients have not been sufficiently evaluated. We hypothesized that mortality shows a variability associated with country after adjustment for clinical characteristics and management. Methods: Analysis of four studies carried out at 6-year intervals over an 18-year period. The studies included 26,024 patients (5183 in 1998, 4968 in 2004, 8108 in 2010, and 7765 in 2016) admitted to 1253 units from 38 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 42 publications
2
41
0
4
Order By: Relevance
“…32 Weaning strategies in patients with AECOPD are quite limited at present (►Table 1). A subanalysis of 189 patients with AECOPD receiving invasive mechanical ventilation who were included in an international observational study of mechanical ventilation in the ICU in 2016 15 showed a significantly higher use of gradual reduction of pressure support as weaning method than the spontaneous breathing trial (56.1 vs. 43.9%, p < 0.001). Weaning was defined as difficult in 25.4% of patients and prolonged in 2.1%.…”
Section: Weaning Strategies and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Weaning strategies in patients with AECOPD are quite limited at present (►Table 1). A subanalysis of 189 patients with AECOPD receiving invasive mechanical ventilation who were included in an international observational study of mechanical ventilation in the ICU in 2016 15 showed a significantly higher use of gradual reduction of pressure support as weaning method than the spontaneous breathing trial (56.1 vs. 43.9%, p < 0.001). Weaning was defined as difficult in 25.4% of patients and prolonged in 2.1%.…”
Section: Weaning Strategies and Outcomesmentioning
confidence: 99%
“…11 AECOPD is among the most common cause of medical admission to hospital, and patients with frequent exacerbations have accelerated lung function decline, worse quality of life, and greater mortality. [12][13][14][15][16][17] About half of COPD exacerbations are caused or triggered primarily by bacterial and viral infections (especially from rhinovirus), but air pollution may also be an important trigger. 14 Among patients with AECOPD, admission to an intensive care unit (ICU) is common.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They also have a major economic impact. According to cohort studies that enrolled unselected critically ill patients receiving mechanical ventilation (invasive or non-invasive) for more than 12 h [1], the proportion of patients managed for COPD exacerbation decreased from 10% in 1998 to 7% in 2016 ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Severe asthma exacerbation causing respiratory failure may lead to major mechanical ventilation-associated complications (e.g., barotrauma, cardiovascular collapse, atelectasis, and pneumonia) that can impact on morbidity and mortality. Severe asthma exacerbation accounts for approximately 1% of mechanically ventilated patients admitted to the ICU [1]. NIV use in these patients increased from 3% in 1998 to 34% in 2016 [2].…”
Section: Introductionmentioning
confidence: 99%